The production of craters on the mid-sized Saturnian satellites by Centaur objects - Di Sisto, Romina Paula (2013)
Context. The Saturnian satellite system has been observed in detail by the Cassini-Huygens mission. These satellites present different surface features, including impact craters caused by small objects probably coming from the trans-Neptunian region. Aims. In this paper we calculate the production of craters on the mid-sized Saturnian satellites produced by Centaurs from the scattered disk (SD) and plutinos in order to determine this contribution, and we compare our estimations with the Cassini observations. Methods. We used a method developed in a previous paper that uses a numerical investigation of the dynamical evolution of Centaur objects to calculate the production of craters. We used a size-frequency distribution (SFD) of scattered disk objects (SDOs) as a power law with a break at diameters d = 60 km considering two cases for the differential power-law index: s2 = 2.5 and s2 = 3.5 for d < 60 km. Results. We calculated the number of craters, the greatest crater produced by Centaurs from the SD and plutinos, and the present cratering rate on each of the mid-sized satellites, for both cases of the SFD of SDOs considered. The contribution of plutinos is negligible compared to SDOs. From our calculations and the comparison with observations we note that the calculated number of craters for s2 = 3.5 is in general nearer the observed number. However, in general for smaller craters, the observed number is less than the calculated one. This trend can be explained by at least two mechanisms. On the one hand, this could be caused by an erasing process that gradually buries the craters, which does not affect large craters. On the other hand, the comparison of the calculated and observed crater size-frequency distribution for different size ranges implies that for d < 60 km, the SFD of SDOs is consistent with the assumed index s2 = 3.5, for d ≥ 0.2-1.4 kmand for d ≤ 0.2-1.4 km, it is consistent with s2 = 2.5. Then in the range d ~ 0.2-1.4 km, the SFD of SDOs could have a new break. This change of slope could explain the reduction of small craters, at least for some cases. Conclusions. We found a good agreement when comparing our results with observations. However, independent determination of surface ages and geological processes are needed to determine if there is a new break on the SFD of SDOs, if there is a planetocentric source of craters in the Saturnian system, and which craters are primordial.